Free application campaigns as policy interventions: a case study of Kansas Free Application Days - Knox, Mistie Dawn (My University, 2026)
Access to postsecondary education remains unevenly distributed across socioeconomic, geographic, and demographic lines, with financial and procedural barriers continuing to constrain college going opportunities for low-income, first generation, rural, and underrepresented students. Among these barriers, college application fees represent a critical but understudied point of friction in the transition from high school to higher education. In response, states have increasingly adopted free college application campaigns; however, limited empirical evidence exists regarding whether such initiatives expand access or simply redistribute applications among institutions. In addition, little research has examined how school level implementation and counselor support shape the reach and equity of these initiatives across different local contexts. This policy analysis case study examined the Kansas Free Application Days initiative, a statewide, centrally coordinated fee-waiver campaign that allowed students to apply to all public and participating private institutions without cost during a designated three-day window. Guided by Hossler and Gallagher’s (1987) three-phase model of college choice and Bandura’s (1986) social cognitive theory, the study investigated how free application days influence students’ decisions to apply to college and how school counselor practices shape policy implementation and student participation. Data sources included a questionnaire administered to Kansas high school seniors and structured interviews with school counselors across rural, suburban, and urban contexts. Student questionnaire responses were analyzed descriptively to identify patterns in application behavior and motivation, while counselor interviews were analyzed thematically to examine implementation practices, local capacity, and equity considerations. Findings from these sources were integrated to evaluate the policy’s design, delivery, and outcomes across diverse school settings. Results suggest that Kansas Free Application Days reduced perceived financial risk and encouraged broader application behavior for many students, including institutions students initially perceived as out of reach. The initiative also helped normalize the college application process within schools by creating structured opportunities for students to apply alongside peers and seek guidance from counselors. The designated three day application window further created a clear and time bound signal that this was the moment to apply, generating a sense of urgency that prompted students to take action. Although counseling staff expressed strong support for Kansas Free Application Days, the initiative’s impact varied based on how it was embedded within existing school structures including scheduling, counselor capacity, and availability of direct application support for students. These findings indicate that fee elimination alone is insufficient to ensure uniform access and underscore the importance of aligning financial interventions with school-level supports to meaningfully expand postsecondary opportunity.
Keywords: College access; Free application fees; First generation; Fee waiver; Application fees